Optimum time for angle visualization during ab interno glaucoma surgery: Before or after phacoemulsification. Issue 5 (May 2019) - Epstein, Rebecca S.; Scott, Anthony T.; Young, Cara E. Capitena; Patnaik, Jennifer L.; Pantcheva, Mina B.; SooHoo, Jeffrey R.; Kahook, Malik Y.; Seibold, Leonard K.
Abstract : Purpose : To determine whether it is more advantageous to perform ab interno glaucoma surgeries involving the angle before or after phacoemulsification. Setting : University of Colorado Health Eye Center, Aurora, USA. Design : Retrospective case series. Methods : Video recordings were taken of eyes having phacoemulsification with or without angle surgery. From the videos, still images of the angle before and after cataract surgery were obtained. Four glaucoma physicians independently reviewed the images and were masked to whether the images presented side‐by‐side were captured before or after cataract surgery. The reviewers used a 5‐point rating scale to assess which of the 2 presented images showed the best visualization of the angle. Patient and ocular characteristics were analyzed to determine predictive factors for better view before or after phacoemulsification. Results : Twenty side‐by‐side comparisons (20 eyes of 20 patients) were reviewed and rated. The mean rating of all surgeons was 2.93, nearing the "3‐no difference" response. The most common response was "3‐no difference" between each photograph (32.5%), followed by "4‐post phacoemulsification image somewhat better" (30%), and "2‐pre‐phacoemulsification image somewhat better" (27.5%). No ocular characteristic, including anterior chamber depth, angle pigmentation, or cumulative dissipation energy, was found to be predictive of surgeon preference. Conclusion : In combination phacoemulsification and angle‐based glaucoma procedures, there appears to be no significant angle visualization difference whether the surgeon chooses to complete angle surgery before or after phacoemulsification; therefore, the decision of surgical order should rely on surgeon preference.